Entrepreneurial Intention Model of Learning and Self-Efficacy Aspects - Kurjono, Kurjono; Yuliyanti, Leni; Saripudin, Saripudin (Dinamika Pendidikan, 2020)
The purpose of this study is to unearth the effect of entrepreneurship learning on entrepreneurial intentions mediated by self-efficacy, and to find out the differences in entrepreneurial intentions viewed from the gender aspect. The research method employed in this study was an explanatory survey method. With respect to the research population, 560 accounting education students from all over Indonesia took part in this study by using the sample size technique of Isaac Michael so that the sample size was 233 respondents. The research samples taken from the population of accounting education students in Indonesia consisted of the students from Unimed, UPI, UNY, UNM, UM Malang and Unesa Surabaya. The data were collected using questionnaires in a google form and the validity and reliability of the collected data had also been tested. In this study, descriptive analysis and path analysis were employed as the data processing technique. The results showed that entrepreneurship learning and self-efficacy had a significant positive effect on entrepreneurial intentions. In particular, self-efficacy had the greatest effect on entrepreneurial intentions. There is no difference in entrepreneurial intentions based on the gender aspect. It is recommended to increase entrepreneurship learning through facilities and infrastructure indicators, self-efficacy through generally indicators, and entrepreneurial intentions through the indicators of spirit to try entrepreneurship.